Volatility of GDP, macro applications and policy implications of real options for structure of capital markets - José Pablo Dapena (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
The traditional marshallian rule of investing (abandoning) when the value of an underlying asset is above (below) the cost of an alternative investment is modified in the presence of uncertainty and irreversibility giving rise to an option component into decisions. This component is affected by the degree of volatility of underlying assets, which in turn can derive their volatility from the economy as a whole, affecting the investment process and therefore the accumulation of capital and future growth. In the same tense, the evidence of volatility in the returns of the underlying assets of the economy affects the market value of debt contracts, conveying recommendations regarding the financial architecture of the economy and the type of financial instruments better suited. The paper explores the application of contingent claims analysis both to the potential effect of macro volatility on aggregate investment, and to the effect on the presence of high levels of indebtedness of the economy, with a special application to the Argentinean economy where we obtain that economies with high level of volatility would require a significant level of internal saving and capital markets driven mainly by equity instruments of financing, which helps to better accommodate uncertainty by means of the price of assets.
Keywords: G00; F36; O16; 330; volatility; contingent claims; real options; aggregate investment; saving; capital markets